Synthesis, Characterization of 4-Anilino-6,7-Dimethoxy Quinazoline Derivatives as Potential Anti-Angiogenic Agents - Devegowda, Preethi S.; Balaji, Kyathegowdanadoddi Srinivasa; Prasanna, Doddakunche Shivaramu; Swaroop, Toreshettahally Ramesh; Kameshwar, Vivek Hamse; Jayarama, Shankar; Siddalingaiah, Lokesh; Rangappa, Kanchugarakoppal Subbegowda (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Quinazolines are a big family of heterocyclic compounds with anti-cancer properties. Objective: The latest investigation was on synthesis, characterization of novel 4-anilinoquinazoline derivatives for their anti-angiogenic effect. Method: A series of novel 4-anilino-6,7-dimethoxy quinazoline derivatives were synthesized and characterized using 1H, 13C NMR, FT-IR and LC-MS techniques. Cytotoxicity assays were performed for all compounds against different cell lines such as Human colon carcinoma (HCT116), Human chronic myeloid leukemia (K562) and Human breast cancer (SKBR3) cell lines using 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyl tetrazolium Bromide (MTT), Trypan blue and Lactose dehydrogenase release assay. The selected compounds were evaluated for their anti-tumor and anti-angiogenic effect on EAC tumor model. The molecular docking studies were drawn using maestro 2D sketcher and energy minimize was compounded by OPLS 2005. Results: Among all compounds, RB4 and RB7 showed moderate activity whereas RB1 showed most potent activity comparable with that of the standard drug cisplatin against all three cell lines. RB1 also inhibited the proliferation of tumor cells in three different cell lines. Further, in-vivo studies revealed that RB1 significantly reduced secretion of ascites, tumor cell proliferation and increased the life span of tumor bearing mice. The antiangiogenic effect of RB1 was revealed from the reduced vessel sprouting in the peritoneum region of treated mice and induced avascular zone in chorioallantoic membrane (CAM) model. The insilco molecular docking studies clearly demonstrate the dual inhibitory potential of RB1 against VEGFR-2 and EGFR from binding to the active site of its receptors. Conclusion: However these studies clearly show that RB1 might be a potent antitumor and anti-angiogenic agent representing a promising lead for further optimization and elucidation of the mechanism of action.
Keywords: Quinazolines